Pengaruh Persepsi, Promosi, dan Pengetahuan Terhadap Keputusan Memilih Produk Pegadaian Syariah dengan Kepercayaan Sebagai Variabel Mediasi: Studi pada Pegadaian Syariah Cabang Way Halim Bandar Lampung - Umi Puspita Sari; Syamsul Hilal; Vicky F Sanjaya (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the influence of perception, promotion, and knowledge on customers’ decision-making at Pegadaian Syariah Way Halim in Bandar Lampung, with trust serving as a mediating variable. A total of 99 customers were selected through purposive sampling to participate in the study. Data were collected using structured questionnaires and analyzed using Structural Equation Modeling (SEM) via SmartPLS version 4. The findings indicate that both perception and knowledge have a positive and significant effect on decision-making through trust as a mediating variable, highlighting the crucial role of trust in shaping customer decisions. In contrast, promotion was found to have no significant direct impact on decision-making. Furthermore, trust was shown to effectively mediate the relationship between perception and knowledge and customers’ decision-making, emphasizing the importance of building trust through accurate information and credible service in financial transactions.